Evaluation of ITGA3 as a Biomarker of Progression and Recurrence in Papillary Thyroid Carcinoma - Zhang, Guoliang; Li, Bing; Lin, Yuanmei (Frontiers in Oncology, 2022)
Objective To investigate the expression of ITGA3 and its association with clinical outcomes in papillary thyroid carcinoma (PTC).Methods The expression level, association with clinicopathologic characteristics, and signaling pathway and gene ontology of ITGA3 and its co-expressed genes in PTC was comprehensively analyzed using bioinformatics analysis through multiple public gene databases. Clinicopathologic data was analyzed to assess the expression difference of ITGA3 in different lymph node stage and the prognostic value of ITGA3 in PTC .Results Data mining based on the Oncomine database revealed that ITGA3 expression in classical PTC and tall cell variant PTC is much higher than in normal thyroid tissue except the follicular variant PTC. Analysis based on the Cancer Genome Atlas (TCGA) database showed that the expression of ITGA3 varies greatly in pathological stages, pathological types, and lymph node stages of thyroid carcinoma. The expression level of ITGA3 in N1 stage is greater than that in N0 stage in PTC (P＜0.05). Survival analysis showed that ITGα3-positive patients with papillary thyroid cancer had a poorer relapse-free survival (RFS) than that of ITGα3-nagetive patients (P<0.01). Multivariate analysis using Cox proportional hazard model showed that ITGα3 positivity, tumor infiltration, and lymph node metastasis were independent risk factors for thyroid papillary carcinoma recurrence. Conclusion ITGA3 is over-expressed in PTC，especially in those with lymph node metastasis, and was associated with poor RFS of PTC . High expression of ITGA3 may have the potential role for predicting PTC lymph node metastasis and recurrence.